How Do Entrepreneurship Education, Innovation, and Subjective Norms Influence Entrepreneurial Interest Through Self-Confidence Among University Students? - Isma, Andika; Diarra, Salim (Pinisi Journal of Entrepreneurship Review, 2025)
In today’s complex global environment, entrepreneurship plays a crucial role in driving economic growth and creating job opportunities. Recent trends show that young generation, particularly university students, hold significant potential to become future entrepreneurs. However, in Indonesia, the level of entrepreneurial interest among students remains relatively low compared to that in developed countries. This highlights the urgency to develop a supportive entrepreneurial ecosystem, especially within higher education. This study aims to investigate the direct and indirect effects of entrepreneurship education, innovation, and subjective norms on entrepreneurial interest, with self-confidence as a mediating variable. A quantitative explanatory approach was used, involving 103 students selected through proportional random sampling from a public university. Data was collected via an online structured questionnaire and analyzed using path analysis techniques. The results indicate that entrepreneurship education, innovation, and subjective norms significantly influence entrepreneurial interest both directly and indirectly through self-confidence. Self-confidence also demonstrates a significant mediating role, enhancing the pathway from psychological and contextual factors to entrepreneurial interest. These findings provide actionable insights for educators and policymakers to design more comprehensive entrepreneurship programs that foster innovation and psychological readiness. Encouraging self-confidence among students could be a key strategy to bridge the gap between entrepreneurial potential and interest in higher education.